The Marmaduke Problem: A Case Study of Comics as Linked Open (Meta)data - Topham, Kate; Chambliss, Julian; Wigard, Justin; Huff, Nicole (KULA)

(untitled) (University of Victoria Libraries, 2022)
Michigan State University (MSU) is home to one of the largest library comics collections in North America, holding over three hundred thousand print comic book titles and artifacts. Inspired by the interdisciplinary opportunity offered by digital humanities practice, a research collaborative linked to the MSU Library Digital Scholarship Lab (DSL) developed a Collections as Data project focused on the Comic Art Collection. This team extracted and cleaned over forty-five thousand MARC records describing comics published in Canada, Mexico, and the United States. The dataset is openly available through a GitLab repository, where the team has shared data visualizations so that scholars and members of the public can explore and interrogate this unique collection. In order to bridge digital humanities with the popular culture legacy of the institution, the MSU comics community turned to bibliographic metadata as a new way to leverage the collection for scholarly analysis. In October 2020, the Department of English Graphic Possibilities Research Workshop gathered a group of scholars, librarians, Wikidatians, and enthusiasts for a virtual Wikidata edit-a-thon. This project report will present this event as a case study to discuss how linked open metadata may be used to create knowledge and how community knowledge can, in turn, enrich metadata. We explore not only how our participants utilized the open-access tool Mix’n’match to connect the Comic Art Collection dataset to Wikidata and increase awareness of lesser-known authors and regional publishers missing from OCLC and Library of Congress databases, but how the knowledge of this community in turn revealed issues of authority control.